2018
DOI: 10.3390/atmos9080288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dust Aerosol Retrievals Using Satellite Data in Central Asia

Abstract: Several long-term monitoring of aerosol datasets from the Moderate Resolution Imaging Spectroradiometer (MODIS) on board Terra/Aqua, Multi-angle Imaging SpectroRadiometer (MISR), Sea-Viewing Wide Field-of-View Sensor (SeaWiFS) were used to derive the dust aerosol optical depth (DOD) in Central Asia based on the Angstrom exponent parameter and/or the particle shape. All sensors agree very well on the interannual variability of DOD. The seasonal analysis of DOD and dust occurrences identified the largest dust lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 64 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Most DOT values are ≤ 0.2. This is in agreement with findings of Li and Sokolik (2018). These authors concluded from in-depth analysis of long-term spaceborne passive remote sensing over Central Asia that most DOTs are below 0.2 at 550 nm.…”
Section: Aerosol Optical Properties: Aot Dot and Particle Extinctiosupporting
confidence: 92%
See 2 more Smart Citations
“…Most DOT values are ≤ 0.2. This is in agreement with findings of Li and Sokolik (2018). These authors concluded from in-depth analysis of long-term spaceborne passive remote sensing over Central Asia that most DOTs are below 0.2 at 550 nm.…”
Section: Aerosol Optical Properties: Aot Dot and Particle Extinctiosupporting
confidence: 92%
“…Although Central Asia is a hot spot region of severe environmental problems and potentially dramatic climate-change effects, only a few observational studies on atmospheric aerosols were performed so far (e.g., Pachenko et al, 1993;Golitsyn and Gillette, 1993;Chen et al, 2013; and with a focus on Tajikistan by Abdullaev and Sokolik, 2019). The first systematic characterization of atmospheric aerosol, pollution, and dust conditions in terms of maps of aerosol optical thickness (AOT) and Ångström exponent (AE, describ-ing the spectral dependence of AOT) for Central Asia was recently presented by Li and Sokolik (2018) and Rupakheti et al (2019). AOT is a proxy for the tropospheric aerosol burden in the vertical column and AE can be used to identify and separate dust and non-dust fine-mode aerosol pollution fractions in the observed aerosol mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collocated lidar measurements ( Figure 2) showed thinner layers of dust over Cluj-Napoca at 10:13 UTC, while thicker layers were observed two hours later (Figure 3). Both AOD and Ångström Exponent satellite data showed strong correlation with the equivalent AERONET parameters [58]. [59].…”
Section: Modis Data Analysismentioning
confidence: 92%
“…Trajectories were run every 6 h. (Mikhalenko et al, 2015). A study focusing on the long-term trend of black carbon in the Elbrus ice (Lim et al, 2017) is currently underway as well as several studies investigating additional chemical species, including investigations of calcium and of sulfate. Data are discussed in two companion papers including the glaciochemistry of the deep Elbrus ice core drilled in 2009 (Preunkert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%